2017
DOI: 10.1007/s10396-017-0808-3
|View full text |Cite
|
Sign up to set email alerts
|

A case of Kawasaki disease presenting as sigmoid colitis

Abstract: Initial gastrointestinal symptoms might confuse the clinical pictures of some patients with Kawasaki disease (KD) and delay diagnosis and treatment, especially when the patient does not fulfill sufficient diagnostic criteria for KD. Here, we present the case of a 4-year-old boy with KD who complained of severe left abdominal pain and fever alone for the first 6 days. Abdominal ultrasonography showed severe wall thickening localized to the sigmoid colon, and these findings were confirmed by computed tomography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…2,5,13,16,17,[20][21][22]24,33 The outcome was good in 28 patients (57%, including the 3 patients who did not receive medical treatment). 4,6,12,17,19,[21][22][23][24]27,[29][30][31][32][33][34] Seven patients (14%) showed persistence of CAAs, 5,15,16,20,21 and 1 (2%) patient developed cyanosis, and later, left hand and forefoot gangrene. 3 Three patients (6%) died: in 1 case autopsy revealed massive liver necrosis and progressive duodenal infarction with systemic arteritis and periarteritis involving vessels of all sizes 3 ; the second patient died 2 days after the exploratory laparotomy 2 ; the third patient died because of Pseudomonas septic shock.…”
Section: Resultsmentioning
confidence: 99%
“…2,5,13,16,17,[20][21][22]24,33 The outcome was good in 28 patients (57%, including the 3 patients who did not receive medical treatment). 4,6,12,17,19,[21][22][23][24]27,[29][30][31][32][33][34] Seven patients (14%) showed persistence of CAAs, 5,15,16,20,21 and 1 (2%) patient developed cyanosis, and later, left hand and forefoot gangrene. 3 Three patients (6%) died: in 1 case autopsy revealed massive liver necrosis and progressive duodenal infarction with systemic arteritis and periarteritis involving vessels of all sizes 3 ; the second patient died 2 days after the exploratory laparotomy 2 ; the third patient died because of Pseudomonas septic shock.…”
Section: Resultsmentioning
confidence: 99%
“…Abdominal ultrasound, a computed tomography scan and colonoscopy showed severe thickening of the sigmoid colon. The boy subsequently exhibited typical symptoms of Kawasaki disease and was successfully treated with intravenous immunoglobulins 23 . Several studies have reported hepatobiliary dysfunctions, including hepatitis, cholangitis, jaundice or significantly elevated aminotransferase in Kawasaki disease 22‐24 .…”
Section: Resultsmentioning
confidence: 99%
“…19,22 Abdominal distension, paralytic ileus, hepatomegaly and hydrops of ease. [22][23][24] Hydrops of the gallbladder has been frequently described.…”
Section: Gastrointestinal Featuresmentioning
confidence: 99%
“…Except for the typical five clinical features, KD could have multiple other manifestations including arthritis, aseptic meningitis, colitis, etc [9][10][11] . Indeed, KD in early stage with atypical manifestations often leads to misdiagnosis.…”
Section: Discussionmentioning
confidence: 99%